POST-MOWING AND SEQUENTIAL HERBICIDE APPLICATION IN THE MANAGEMENT OF SOURGRASS (Digitaria insularis) - da Silva, Walison Gasparelo; Moterle, Lia Mara; dos Santos, Renato Frederico (Chilean Journal of Agricultural & Animal Sciences, 2025)
The excessive use of glyphosate in crop production has led to the emergence of sourgrass (Digitaria insularis) populations resistant to this herbicide. The species has a high capacity for emergence and development throughout the year, making it difficult to control during the off-season. The objective of the this study was to evaluate the effectiveness of glyphosate application, alone or in mixture, integrated with post-mowing management or sequential herbicide application for the control of sourgrass in fallow areas in Paraná State, Brazil. The experiment was carried out in a 2 × 5 factorial scheme (with or without mowing × herbicides), under a complete block experimental design with randomized treatments, with four replications. Herbicide applications were made on the reshoots of the mowing management treatment when plants reached a height between 10 and 20 cm. In the unmowed plants, after the initial herbicide application (glyphosate + graminicides), a sequential application of paraquat was performed. Sourgrass control was determined at 7, 14, 21, 28 and 35 days after application, DAA). The results revealed that mowing D. insularis followed by the combined application of glyphosate and other herbicides is a good strategy for the management of this weed. The combined application of glyphosate + clethodim (1480 + 248 g a.i. ha-1), followed by a sequential application of paraquat, was effective in controlling sourgrass and produced results comparable to mechanical management.